OPTIMIZATION OF METHODS OF TREATMENT AND PREVENTION OF POLYPOSIS RHINOSINUSITIS (World Bulletin of Public Health, 2024)
According to the revealed changes in the indicators of hemostasis and blood rheology, the state of intestinal microflora, signs of immune inflammation, evaluation of the obtained results, the validity of the application of disaggregants, probiotics, and gravitational blood methods is shown. The obtained research results are the determining criterion for the developed by us combined method of anti-recurrence treatment and prevention of polyposis rhinosinusitis.